The impact of contactless payment on cash usage at an early stage of diffusion - Tobias Trütsch (Swiss Journal of Economics and Statistics, 2020)
This paper explores the impact of contactless payment on consumers' demand for cash at an early stage of diffusion. The specific devices that are investigated are debit and credit cards, in which the feature is embedded. A novel balanced panel dataset drawn from representative surveys on consumer payment behavior in the USA from 2009 to 2013 is analyzed to account for unobserved heterogeneity in cash usage. The results show that contactless credit and debit cards exert no statistically significant effect on cash usage after controlling for unobserved heterogeneity. Consumers' decision to use contactless payment is an endogenous choice. Card-affined individuals replace conventional card payments with contactless card payments. Hence, the overall effect on cash usage remains unaffected.
Keywords: C33; D12; E41; E42; 330; Contactless payment; Money demand; Cash usage; Credit cards; Debit cards